2020
DOI: 10.1002/adem.202000034
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Fatigue of Ultrafine‐Grained Ferritic/Martensitic Steel

Abstract: The impact of equal‐channel angular pressing in combination with additional heat treatment on microstructure and fatigue of ferritic/martensitic steel is investigated. It is shown that the formation of both the ultrafine‐grained (UFG) structure with an average grain size of about 0.8 μm and the enhanced share of boundaries with the coincidence site lattice (CSL) relationships (the CSL boundaries) leads to an increase in the fatigue endurance limit of more than 50% compared with samples after tempering. Dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…From the microstructure of the samples subjected to CR + requenching ( Table 2 ), numerous microtwins can be observed, which, in this instance, suppresses the overall crack growth as it is splitting into several microcracks. It has recently been demonstrated that the formation of the ultrafine-grained structure and microtwins by using equal-channel angular pressing leads to the enhancement of the fatigue endurance limit [ 16 ]. This work demonstrated that the formation of microtwins can enhance fatigue life in the structures containing elongated grains in a material subjected to CR ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From the microstructure of the samples subjected to CR + requenching ( Table 2 ), numerous microtwins can be observed, which, in this instance, suppresses the overall crack growth as it is splitting into several microcracks. It has recently been demonstrated that the formation of the ultrafine-grained structure and microtwins by using equal-channel angular pressing leads to the enhancement of the fatigue endurance limit [ 16 ]. This work demonstrated that the formation of microtwins can enhance fatigue life in the structures containing elongated grains in a material subjected to CR ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The standard heat treatment procedure for steels with a content of 9–12% Cr is quenching, i.e., heating above the temperature of phase transitions with rapid cooling [ 16 ]. The subsequent high-temperature tempering relieves internal stresses and leads to greater structure equilibrium.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, several researchers have fully discussed the characteristics of fatigue behavior for welded joints from the perspective of empirical, analytical, and numerical solutions. [22][23][24][25][26][27][28] Due to size effect, most of the samples used in fatigue tests are small-sized samples, and the smallsized samples are difficult to fully reflect the stress concentration and stress gradient of the actual structures, leading to difficulties in understanding the relationship between IFs and fatigue properties. [29,30] Although various classical methods have achieved fruitful results, these methods usually adopt some simplified assumptions, [31,32] which make it difficult to fully consider the impact of comprehensive factors on fatigue performance; thus, a general method for variable service conditions is required.…”
Section: Introductionmentioning
confidence: 99%